Statyka i Stateczność Pryzmatycznych Powłok Ramowo-Kratowych - Gutkowski, W. (Engineering Transactions, 1961)
This paper contains the equations for the determination of the forces, displacements and stability conditions for a shell with a regular net of bars. In particular, the stability of a quadratic shell subjected successively to axial compression and torsion is considered. From these considerations it follows that such a shell, compressed by an axial force loses, its flexural-torsional stability similar to that appearing during the torsion of the classical cylindrical shell. All the equations are expressed in the difference form. In conclusion the paper contains a description and the results of an experiment on five-segment shell compressed by an axial force.